(untitled) (AYUSHDHARA, 2023)
The disease Amavata simulate with Rheumatoid Arthritis (RA) in modern parlanceis a symmetric, inflammatory, peripheral polyarthritis of unknown etiology with systemic involvement caused by the impairment of Agni (digestive fire), formation of Ama (bio-toxin) and vitiation of Vata Dosha. The disease Amavata (rheumatoid arthritis) still is a challenge to the physician due to its chronicity, incurability, complications, morbidity and crippling nature. A clinical study was conducted for 45 days at V.Y.D.S Ayurved Mahavidyalaya, Khurja, on 30 patients divided them into two groups of 15 each, to compare the efficacy of Shatyadi kwatha with the well-established control drug Maharasnadi Kwatha in the management of Amavata (rheumatoid arthritis). The demographic data of this study reveals that Amavata (rheumatoid arthritis) can begin at any age, but incidence increases with age. It clearly shows the predominance of the disease in females, in housewives, in addiction of tea/coffee and in Samashana group (consuming suitable and unsuitable foods mixed together). The clinical data of this study reveals that, both the drugs were found capable to enforce relief, but based on % of improvement and clinical assessment of result, it can be concluded that control drug (Maharasnadi Kwatha) was more effective than trial drug (Shatyadi kwatha) in most of the sign and symptom of the disease at extremely significant level.